Public art : the enrichment of Genius Loci / Muhammad Falihin Jasmi, Nur Huzeima Mohd Hussain and Siti Syamimi Omar - Muhammad Falihin, Jasmi; Nur Huzeima Mohd, Hussain; Siti Syamimi, Omar (Universiti Teknologi MARA, Perak, 2018)
Cultural, heritage and religious of a nation becomes significant component towards portraying the genius loci. Presently, public art become a trend to emboss the local distinctiveness through implementation of two-dimensional and three-dimensional art in the city. Despite of the robust city’s development, local authorities with collaboration of various parties had done many public art projects that expose the city’s identity whilst becoming the tourist’s attraction. Thus, this paper reviews several public art projects in Malaysia, as reference studies; identify its contribution to the genius loci betterment and determine the prominent element of the city that being transformed into public art. Hence, it is hoped to improve the quality of public art implementation in the future that commendably reflecting the city’s identity towards improving the place making and becoming the community’s pride.